PENEGAKAN DIAGNOSIS TUBERKULOSIS ANAK DI PUSKESMAS BANDAR KHALIFAH KABUPATEN DELI SERDANG TAHUN 2014 - 2015 - CINDY CLARA AWE; H. DELYUZAR (LP2MTBM MAKARIOZ, 2020)
Tuberculosis (TB) in children is a particular problem which is different from TB in adults. The development of TB disease inchildren is currently very rapidly. At least 500,000 children in the world suffering from TB every year. In Indonesia kasusTBproportion of children among all TB cases in 2010 was 9.4%, then to 8.5% in 2011 and 8.2% in 2012. In the diagnosis of TBin children, all diagnostic procedures can be done, namunapabila encountered limitations of available diagnostic, may use adifferent approach known as the scoring system. TB high incidence of children in Deli Serdang, encourage researchers tofind out how the child's diagnosis of TB in Puskesmas Bandar Khalifah District of Deli Serdang years 2014-2015.This research to know how the diagnosis of TB in children Bandar Khalifah Health Center Deli Serdang years 2014-2015.This study is descriptive. The design is done is a cross sectional study. Researchers assessed the diagnosis of TB inchildren Bandar Khalifah Health Center Deli Serdang, by using secondary data and total sampling method. All medicalrecord files contained child TB in Puskesmas Bandar Khalifah Deli Serdang years 2014-2015 were collected and then do therecording. From the results obtained penellitian enforcement of child TB diagnosis in Puskesmas Bandar Khalifah DeliSerdang of 135 respondents who diagnose children TB amounted to 94 people with a percentage (69.6%). enforcement ofTB diagnosis in children by using the tuberculin skin test result is positive is 67 people (49.6%), while those with negative testresults tuberkulinnya child TB diagnosis by 27 people with the percentage (20.0%), and the child using the TB TB scoringchildren who screen positive are 94 people (69.6%), while the results of scoring TB negative children with TB diagnosis childof this data can not be found.